Research on Energy Harvesting Communication System - Jian Feng; Pingyang Wang; Lin Wang; Xing Zhang (Dianxin kexue)
Energy harvesting（EH）is becoming a promising technology for future wireless communication network for its potential of saving nonrenewable energy and making the communication environmentally friendly. However, due to the unpredictable and intermittent nature of energy source, the capacity of storage devices, as well as the unpredictable nature of the communication channel and users' arriving data, the road to the communication system powered solely by harvested energy is plagued with potholes. Despite this, remarkable progress has been made in applying energy harvesting to wireless communications. An extensive survey on the current development status and main research fields was made, and the most common used model, system framework and optimization methods were analyzed carefully. Finally the future development for applying EH to communication systems was concluded.